2017
DOI: 10.1016/j.bbacli.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative activity of high-density lipoprotein (HDL): Mechanistic insights into potential clinical benefit

Abstract: Uptake of low-density lipoprotein (LDL) particles by macrophages represents a key step in the development of atherosclerotic plaques, leading to the foam cell formation. Chemical modification of LDL is however necessary to induce this process. Proatherogenic LDL modifications include aggregation, enzymatic digestion and oxidation. LDL oxidation by one-electron (free radicals) and two-electron oxidants dramatically increases LDL affinity to macrophage scavenger receptors, leading to rapid LDL uptake and fatty s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(142 citation statements)
references
References 196 publications
3
109
0
3
Order By: Relevance
“…Study results have indicated that higher activity of PON1 was associated with a lower incidence of major cardiovascular events in humans. HDL-associated LCAT exerts its antioxidative properties via the hydrolysis of oxidized acyl chains from phosphatidylcholine-based oxidized phospholipids and oxidized free fatty acids [34][35][36]. It has been demonstrated that HDL-associated platelet-activating factor acetylhydrolase (PAF-AH) hampers the production and limits the activity of mildly oxidized low-density lipoprotein since it facilitates the hydrolysis of active oxidized phospholipids to lysolipids, which in consequence results in the removal of biologically active lipids in these lipoproteins [37].…”
Section: Hdl Role and Functionsmentioning
confidence: 99%
“…Study results have indicated that higher activity of PON1 was associated with a lower incidence of major cardiovascular events in humans. HDL-associated LCAT exerts its antioxidative properties via the hydrolysis of oxidized acyl chains from phosphatidylcholine-based oxidized phospholipids and oxidized free fatty acids [34][35][36]. It has been demonstrated that HDL-associated platelet-activating factor acetylhydrolase (PAF-AH) hampers the production and limits the activity of mildly oxidized low-density lipoprotein since it facilitates the hydrolysis of active oxidized phospholipids to lysolipids, which in consequence results in the removal of biologically active lipids in these lipoproteins [37].…”
Section: Hdl Role and Functionsmentioning
confidence: 99%
“…The hiSSB group tended to have higher levels of CRP, IL-18, and MCP-1, although the difference in these inflammatory markers between the loSSB and hiSSB groups was not significant. Given that low grade inflammation may play a role as both a cause and consequence of low HDL-C levels [47,48], and higher HDL-C levels may act as a buffer against low-grade inflammation [49][50][51], the lower levels of HDL-C observed in the hiSSB group may have been a consequence of proinflammatory factors modulated by a high sugar dietary pattern.…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49][50] The uptake of oxidized LDL by macrophages via scavenger receptors transforms them into foam cells, which is a marker of atherosclerosis. 51) HDL is responsible for the transport of cholesterol from cells back to the liver and exerts a protective effect against atherosclerosis. It acts as an antioxidative agent, protecting against the generation of oxidized lipids by the action of redox-active Met residues of apoA-I or receiving lipid hydroperoxides from oxidized LDL via SR-BI.…”
Section: Physiological Functions Of Lipoproteinsmentioning
confidence: 99%